Correlation between the Values of Immature Platelet Fraction and Mean Platelet Volume with the Extent of Coronary Artery Disease in Patients with Non-ST-Segment Elevation Myocardial Infarction - Rauf, Shadab; Kumar, Tarun; Kumar, Vijay; Nath, Ranjit Kumar (Journal of Cardiology and Cardiovascular Medicine, 2023)
Introduction: The identification of new markers of thrombotic risk and early diagnosis of Non-ST-segment Elevation Myocardial Infarction (NSTEMI) could allow the optimization of the therapy and predict short and long-term prognosis. Aims and objective: We aimed to assess the impact of Immature Platelet Fraction (IPF) and Mean Platelet Volume (MPV) levels on the extent of Coronary Artery Disease (CAD) in patients with NSTEMI undergoing coronary angiography. Methods: This is a prospective observational study in which 100 subjects of Non-ST Elevation Myocardial Infarction were recruited. For the measurement of platelet count, IPF and MPV samples were analyzed by an automated hematology analyzer (Sysmex XN 1000). Patients were subjected to coronary angiography as per institutional protocol and the extent of coronary artery lesion was noted. Result: A cutoff of MPV (fL) ≥ 10.6 can predict the involvement of the left anterior descending artery (LAD) with a sensitivity of 84%, and a specificity of 50%. With the cutoff of IPF (%) ≥ 2.4, it can even predict the type of disease i.e., Double Vessel Disease (DVD), or Triple Vessel Disease (TVD) with a sensitivity of 97%, and a specificity of 19%. Mean IPF values and MPV levels were significantly higher in patients with LAD involvement i.e., 4.40 ± 1.72% (p = 0.003) and 12.45 ± 1.88 (p = 0.030) respectively than in patients without involvement of LAD i.e., 2.78 ± 1.50% and 11.08 ± 2.19 respectively. Conclusion: Immature platelet fraction and mean platelet volume were significantly associated with the involvement of the left anterior descending artery which was the most commonly involved vessel in patients with NSTEMI. Mean platelet volume was also associated with TVD which was statistically significant. MPV and IPF can be useful early independent hematologic markers to identify patients with a higher risk for significant CAD as they are readily available and inexpensive.